Jumping performances in National 2 women handball players: Effect of a 3-month plyometric training program - Guiard, Q.; Durand, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study investigates both jumping performances (in squat jump (SJ) and counter movement jump (CMJ)) and global lower limbs stiffness in women handball players and reports the effect of a 3-month plyometric training program (length: 45 min, once a week) on these parameters. Mean performance for SJ was 22.3±3.0 cm and for CMJ 29.3±4.1 cm. Lower limbs stiffness reached 21213±7510 N.m-1. There was no correlation between the different parameters. Eight players followed the plyometric program but six were finally evaluated because of injuries. No change was observed for CMJ but lower limbs stiffness and SJ height tend to increase. This suggests that a unique 45-min plyometric training session once a week during three months may not be enough to enhance jumping capacities and lower limbs stiffness in women handball players.